Exploratory Concept Analysis of Urban Mobility - Kumaravel, Avinth Kumar; Löfgren, Hugo (My University, 2023)
Urban mobility is one of the fields under rapid development due to the movement of society towards sustainability and green transport. Drive experience and comfort of the user plays a vital role in the development of these vehicles. This project looks into the future focusing on the development of an urban mobility solution which could act as an alternative for cars inside the city. The standard product development process was opted starting with generation of requirement specifica tions and function analysis. Concept generation was done following that, with the help of ideas generated through innovative methods and final selection of concepts were performed using elimination matrices. The result of the project is a virtual prototype of a three wheeled electric trike concept with the ability to tilt the front part of the vehicle to improve the user feel. Verification of the concept was also done with the help of Finite Element Analysis (FEA) to make sure that the solution was robust enough for usage.
Keywords: Urban mobility, delta trike, electric trike, tilt, lean